An Advanced Information System for Intelligent Agriculture - Thabet Righi; Meftah Mohammed Charaf Eddine (University Of Eloued جامعة الوادي, 2020)
It is essential to increase the productivity of agricultural and farming processes to improve yields and cost effectiveness with new technology such as the Internet of Things (IoT). In particular, IoT can make agricultural and farming industry processes more efficien t by reducing human intervention through automation. In this study, we will study all existing technologies in this domain and then propose an Advanced Information System (AIS) for Smart Agriculture based on the Internet of Things (IoT) IoT), i t takes pre dict ive aspects and makes decisions , in particular to analyse the data (climatic, environmental and financial ...) and to draw critical information from it (diseases, water shortage, inappropriate climate..) to make the most appropriate decision (Agricultu ral Plan, Prevention, treatment, medicines, watering,....) in an intelligent environment. This system will provide real added value to smart agriculture. Finally, we will be able to ensure better crop quality and reduce all of our costs.
Intervention
Keywords: Advanced Information System (AIS); A gricultural S mart farming; Internet of Things ( Predictive analytics Decision System; Expert System